Quantitative study on the effect of stress magnetization of martensite in 304 austenitic stainless steel. (August 2022) - Lan, Xiwang; Hu, Bo; Cheng, Hongzhi; Luo, Weitao; Wang, Shaofei
Highlights: The effect of stress-magnetization on martensite is quantitatively studied. Magnetic domain is observed in 304 austenitic stainless steel. An analytic expression of magneto–mechanical model is established. Abstract: Ferromagnetic materials exhibit a stress-magnetic coupling effect, where mechanical and magnetic energy are converted to each other. This effect is known as the effect of stress-magnetization. The effect of stress-magnetization of 304 austenitic stainless steel after the occurrence of martensitic phase transformation to produce ferromagnetic phase is not clear. To clarify the effect of stress-magnetization of alpha'-martensite and its mechanism. A tensile loading test is designed to evaluate the effect. X-ray diffraction (XRD) and Lorentz transmission electron microscopy (LTEM) methods are used to investigate the evolution of microstructures and clarify the mechanism. Furthermore, an analytical expression model is established on the basis of martensitic transformation dynamics and a magneto-mechanical model. The accuracy of the model is validated from perspectives of martensitic transformation, the effect of stress-magnetization of alpha'-martensite, and their combination. Results showed that the effect of stress-magnetization of alpha'-martensite is significant and increases magnetic signal collected by fluxgate sensor. The mechanism is the increase of magnetization of the material due to stress by assimilating the orientation of magnetic domains. The proposed model demonstrates satisfactory accuracy and provides theoretical bases for evaluating mechanical damage in 304 austenitic stainless steel.